Bus Ticket Booking Application - Edgar Lambert Nakwagala (Uganda Christian University, 2023)
This project report gives a case study on the creation of an application for Uganda's Kayoola Bus Company to buy bus tickets. The application's purpose is to give consumers a simple and convenient way to explore, choose, and buy bus tickets online. The paper goes over the study's history, emphasizing how crucial it is to solve the problems with the traditional bus ticketing system. The application's primary goal is to improve both the overall user experience and operational effectiveness for both bus operators and passengers. The geographic region served by the Kayoola Bus Company in Kampala, Uganda, is included in the study's purview. The part on the literature review offers viewpoints from academic researchers with expertise in e-ticketing systems and the effectiveness of bus ticket reservation systems. Their work helps to comprehend the ecosystem of bus ticketing applications and to pinpoint the variables that affect their profitability. The study's importance is emphasized in the report's conclusion, along with the benefits to customers in terms of ease and accessibility, time savings, and business growth and competitiveness for app developers and service providers. The results of this case study will serve as a basis for more investigation and enhancements to the ecosystem surrounding bus ticket purchasing apps.
This is a dissertation.